Regular and switching platform: Bone stress analysis with varying implant diameter - Vargas, Luis Carlos Merson; De Almeida, Erika Oliveira [UNESP]; Rocha, Eduardo Passos [UNESP]; Kina, Sidney; Anchieta, Rodolfo Bruniera [UNESP]; Freitas Jr., Amílcar Chagas [UNESP]; França, Fabiana Mantovani Gomes (American Academy of Implant Dentistry, 2013)
The aim of this study was to evaluate stress distribution of the peri-implant bone by simulating the biomechanical influence of implants with different diameters of regular or platform switched connections by means of 3-dimensional finite element analysis. Five mathematical models of an implant-supported central incisor were created by varying the diameter (5.5 and 4.5 mm, internal hexagon) and abutment platform (regular and platform switched). For the cortical bone, the highest stress values (rmax and rvm) were observed in situation R1, followed by situations S1, R2, S3, and S2. For the trabecular bone, the highest stress values (rmax) were observed in situation S3, followed by situations R1, S1, R2, and S2. The influence of platform switching was more evident for cortical bone than for trabecular bone and was mainly seen in large platform diameter reduction.
Keywords: Bone; Finite analysis; Implant dentistry; Loading; Stress; dental porcelain; IPS e.max Press; resin cement; Variolink; biological model; biomechanics; chemistry; computer simulation; dental abutment; elasticity; finite element analysis; human; incisor; maxilla; mechanical stress; methodology; physiology; surface property; three dimensional imaging; tooth crown; tooth implant; tooth prosthesis; Biomechanics; Computer Simulation; Crowns; Dental Abutments; Dental Implant-Abutment Design; Dental Implants; Dental Porcelain; Dental Prosthesis Design; Elasticity; Finite Element Analysis; Humans; Imaging, Three-Dimensional; Incisor; Maxilla; Models, Biological; Resin Cements; Stress, Mechanical; Surface Properties